The Power of Tax Authority and Tax Compliance: Does Tax Literacy Matter? - Indah Anisykurlillah; Junjung Sugiyat; Hasan Mukhibad (Jurnal Dinamika Akuntansi, 2024)
Purpose: Our research aims to prove the influence of tax authority power (coercive and legitimate), tax morality, perception of fairness, and religiosity on tax compliance. Also, we test the moderating effect of tax literacy on the influence of the relationship between perceived fairness and coercive power on tax compliance. Methods: This research used 199 respondents determined by convenience sampling, snowball sampling technique. Data were analyzed using Partial Least Squares based Structural Equation Modeling (PLS-SEM). Result: We report that legitimacy power, tax morale, and religiosity positively influence tax compliance. On the other hand, coercive power and perceived fairness do not influence tax compliance. Moreover, our study reports that tax literacy has a role in reducing the influence of perceived fairness on tax compliance. Novelty: Our study contributes to expanding literature in two important ways. First, we re-examined the influence of the power of tax authority on tax compliance of university employees who experienced a change in university status from a public university to a state university with legal entity status (PTN-BH)-causing a change in tax rates. Second, we expand the slippery slope framework by proving the role of tax literacy in increasing the influence of the power of tax authority on tax compliance.